2015
DOI: 10.1021/acs.langmuir.5b03399
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Functionalization of Nanoparticles Synthesized by Gas Aggregation Source: Opening New Routes Toward the Fabrication of Nanoparticles for Biomedicine

Abstract: The need to find new nanoparticles for biomedical applications is pushing the limits of the fabrication methods. New techniques with versatilities beyond the extended chemical routes can provide new insight in the field. In particular gas aggregation sources offer the possibility to fabricate nanoparticles with controlled size, composition and structure out of thermodynamics. In this context, the milestone is the optimization of the dispersion and functionalization processes of nanoparticles once fabricated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…According to the results above, we can speculate that such systems could be developed as auxiliary devices for water remediation or as sensors for detection and concentration measurements . Also, although the subsequent dispersion of such particles, from gas aggregation sources in aqueous solutions, is not an easy task, ultrasonication can assist that purpose …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results above, we can speculate that such systems could be developed as auxiliary devices for water remediation or as sensors for detection and concentration measurements . Also, although the subsequent dispersion of such particles, from gas aggregation sources in aqueous solutions, is not an easy task, ultrasonication can assist that purpose …”
Section: Resultsmentioning
confidence: 99%
“…54 Also, although the subsequent dispersion of such particles, from gas aggregation sources in aqueous solutions, is not an easy task, ultrasonication can assist that purpose. 55…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The most complex construct (C) has the greatest polydispersity. Opera et al studied the dispersion of boron-functionalised nanoparticles using gas aggregation, and found that functionalisation led to an increase in particle dispersion [68].…”
Section: Pyridine-2-thione Assaymentioning
confidence: 99%
“…In general, the elements present in the NPs are similar or the exact ones on the target, but the internal structure of the compounds depends on the atomic diffusion of the two kinds of atoms. As an example, Oprea et al showed the fabrication of Fe-B NPs from a Fe50B50 target, which was made of an internal Fe core while outside the shell with a combination of Fe and B oxides and oxynitrides (Oprea et al 2015). They could be functionalized with polyethylene glycol (PEG) and exhibited superparamagnetic behavior at RT.…”
Section: Physicochemical Approachesmentioning
confidence: 99%